Vacancy diffusion coupled discrete dislocation dynamic modeling of compression creep of micro-pillars at elevated temperature. (1st June 2020) - Wang, Jian; Huang, Minsheng; Zhu, Yaxin; Liang, Shuang; Li, Zhenhuan
Abstract: A two-dimensional discrete-continuous scheme (DCS), which couples the motions of dislocations and diffusion of vacancies, is developed. There are three modules in this scheme. The glide and climb of dislocations are performed by the discrete dislocation dynamics (DDD) module, by which the evolution of dislocations is captured and the plastic strain due to dislocation motions is obtained. The diffusion of vacancies is performed by the finite difference method (FDM) module, by which the vacancy concentration field and the inelastic strain due to vacancy diffusion are obtained. The plastic strain by the DDD and the inelastic strain by the FDM, as the eigen-strains, are transferred to the finite element method (FEM) module, by which the stress field is obtained and then transferred back to the DDD module and FDM module to drive dislocation motions and vacancy diffusion. By this vacancy diffusion coupled discrete dislocation dynamics scheme, the compression creep of single crystalline and bi-crystalline aluminum micro-pillars at elevated temperature is modeled. Some interesting creep behaviors are computationally captured. The compression creep of single crystalline and bi-crystalline micro-pillars is size dependent: the creep strain of micro-pillars at higher compressive stress increases with increasing micro-pillar diameter, which is in good agreement with experimental results reported in the literature. This is believed to result from higher dislocation density in those micro-pillars with larger diameter. Graphical abstract: Image, graphical abstract